2021
DOI: 10.3390/ijms22042046
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Provision of Oxidisable Substrates to the Mitochondria in ME/CFS Lymphoblasts

Abstract: Although understanding of the biomedical basis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is growing, the underlying pathological mechanisms remain uncertain. We recently reported a reduction in the proportion of basal oxygen consumption due to ATP synthesis by Complex V in ME/CFS patient-derived lymphoblast cell lines, suggesting mitochondrial respiratory inefficiency. This was accompanied by elevated respiratory capacity, elevated mammalian target of rapamycin complex 1 (mTORC1) signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 106 publications
2
28
1
1
Order By: Relevance
“…We observed, however, lower levels of ATP5F1E, a complex V subunit. Previous studies in immortalised lymphocytes from ME/CFS patients have shown complex V deficiency and hyperactivation of mTORC1 [31,70]. In addition, downregulation of SLC25A24 can also indicate disturbed ATP synthesis [71].…”
Section: Discussionmentioning
confidence: 98%
“…We observed, however, lower levels of ATP5F1E, a complex V subunit. Previous studies in immortalised lymphocytes from ME/CFS patients have shown complex V deficiency and hyperactivation of mTORC1 [31,70]. In addition, downregulation of SLC25A24 can also indicate disturbed ATP synthesis [71].…”
Section: Discussionmentioning
confidence: 98%
“…The examples provided here suggest that these cells will be useful for the development of diagnostic tests (which in most cases do not exist), identification of drug targets and testing of pharmacological agents, and are a worthwhile model for studying mitochondrial function in neurological disorders. [44,59]…”
Section: Discussionmentioning
confidence: 99%
“…Despite these obvious differences, the methylation pattern and gene expression profiles of lymphocytes are largely maintained in LCLs and display many of the specific characteristics of primary B cells [ 58 ]. This is also true for many diseases, and clear differences in the transcriptomes and the epigenomes of patients and controls have been identified in LCLs for numerous diseases [ 59 , 60 , 61 , 62 , 63 ]. LCLs are increasingly being used as models of disease and given their high oxidative nature, are ideal systems for studying mitochondrial function.…”
Section: Types Of Human Cellular Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could combine with AMPK’s direct inhibitory phosphorylation of the RAPTOR subunit of mTORC1 to inhibit its activity and produce a decrease in cell growth and division [ 97 ]. mTORC1 is known for stimulation of expression of OXPHOS proteins [ 98 , 99 ]; hence, it is likely that the downregulation of OXPHOS components in AMPKα-overexpressing Dictyostelium cells results from the inhibition of mTORC1 activity. Enhanced mitochondrial biogenesis is induced by as yet unidentified mitochondrial protein targets, which, upon direct or indirect phosphorylation by AMPK, leads to dramatic changes in the abundance and/or phosphorylation-dependent activity of mitochondrial proteins involved in energy metabolism, protein synthesis, and membrane biogenesis.…”
Section: Discussionmentioning
confidence: 99%